Health Education for Mothers With Stunting Toddlers About Supplementary Feeding (PMT) in RW 01 Wetan City Village Sub-District Garut Kota - Dadang Purnama; Iwan Shalahuddin; Udin Rosidin; Nina Sumarni; Witdiawati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Stunting is not a minor issue; according to World Bank study, losses owing to stunting range between 3 and 11% of GDP. Economic losses due to stunting in Indonesia are projected to be Rp. 300 T-Rp. 1,210 T per year, with a GDP of Rp. 11000 trillion. The money lost is due to the government having to spend additional funds on noncommunicable disease health insurance and addressing stunting instances. Education's goal is to increase knowledge and support stunting prevention behavior in order to lower stunting rates and prevent the appearance of new stunting cases. Learn more about the challenges faced by the residents of RW 01 Babakan Abid Wetan City in their attempts to avoid and overcome stunting. The lecture technique, question and answer, discussion, and demonstration are all used. The health counseling efforts resulted in roughly 33 women with toddlers. When the content was presented, the therapy participants appeared ecstatic. Participants happily participated in the therapy because it was done in an entertaining way. The counselling activity was beneficial since the participants paid close attention to the information offered. This is demonstrated by the amount of participants that want to answer questions during the question and answer session. Participants willingly participated in the counselling because it was done in a nice face-to-face setting. The counseling activity was beneficial since the participants paid close attention to the information offered regarding Supplementary feeding to prevent stunting.